Breaking Down Communication Barriers: Assessing the Need for Audiologists to Have Access to Clinically Relevant Sign Language - Panning, Samantha; Lee, Rachel L.; Misurelli, Sara M. (Journal of the American Academy of Audiology, 2021)
Background Research suggests Deaf individuals have longstanding negative perceptions of their interactions with health care providers, primarily due to communication barriers. One way to improve relations would be for audiologists to learn clinically relevant sign language.Purpose The aim of the study is to gain a better understanding of audiologists' knowledge of Deaf culture and American Sign Language (ASL) and evaluate motivation for instruction in signing abilities.Research Design A 21-question survey was emailed and advertised in a social media group for audiologists. The survey was divided into four sections: (1) demographics, (2) education of ASL and Deaf culture, (3) experience with ASL and Deaf culture, and (4) motivation to learn clinical signs.Data Analysis Descriptive statistics were analyzed for quantitative analysis of survey responses.Results A total of 489 responses were obtained and analyzed. Majority of respondents (82.6%) completed a manual ASL course, though only a third reported exposure to clinically relevant signs (37.4%). The majority of respondents rated their signing abilities at the word level, and knowing somewhere between 5 and 20 signs, expressively (50.5%) and receptively (53.9%). Results illustrate the majority of audiologists (54.5%) feel their clinical signing abilities need to be improved and were either highly (30.9%) or somewhat motivated (42.1%) to do so.Conclusion Study results suggest that although participants are enrolling in and completing ASL courses, clinical signs are not routinely included. This omission leads to reduced signing ability, potentially harming the provider–patient relationship. The majority of survey respondents reported that they are strongly motivated to improve their signing abilities. Results of the present study suggest there is need for a comprehensive clinical signs resource for audiologists to provide quality patient care to their Deaf patients. At present, there is no known, available tool to help accomplish this need.
Keywords: American Sign Language; audiologists; clinical signs; Deaf culture